QUALITY MANAGEMENT OF EDUCATIONAL INSTITUTIONS ACHIEVEMENT AT IBTIDAIYAH MADRASAH - Aminah, Faiqotul; Putriani, Erin Nur; Fithri, Naylal (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Outstanding Madrasah Ibtidaiyah refers to a primary level educational institution in the Islamic education system that has achieved a high level of excellence and achievement. Aspects include academic, non-academic, and student character development activities. This research was conducted at Madrasah Ibtidaiyah Al-Islamiyah Karanganyar Paiton Probolinggo on quality planning at Madrasah Ibtidaiyah Al-Islamiyah (MIA) Karanganyar Paiton in realizing educational institutions, examining and describing more deeply the implementation of quality at Madrasah Ibtidaiyah Al-Islamiyah (MIA) Karanganyar Paiton in realizing outstanding educational institutions, and examining and describing quality evaluation. The methodology used in this research uses a qualitative approach. Data collection techniques with observation, interviews and documentation. The method used to check the validity of the data is method triangulation. The results of the research showed that: 1). Planning: establishing vision and mission as quality guidelines, commitment to the implementation of national standard schools, comfortable and good service processes, improving the quality of student input, using quality references set by the government, quality planning in management review. 2) Implementation: implementing the national standard curriculum as well as the pesantren curriculum, educators and education personnel with at least a bachelors degree. There is satisfaction from students and parents/guardians of students as users, 100% graduates are absorbed and equipped with expertise, the existence of representative infrastructure, transparent education management, very good and very close relations between schools and communities, the existence of special services to support learning activities. 3). Evaluation: conducting self-assessment of school performance based on accountability, transparency and efficiency